Preparation method of co-fired argyrodite type electrolyte and all-solid-state lithium metal battery
By co-burning different sulfur-silver germanium ore type electrolytes and building conductive interlayers at the interface of lithium metal, the problem of decomposition of sulfur-silver germanium ore type electrolytes at high voltage and incompatible with lithium metal is solved, and the battery performance and safety is improved.
Patent Information
- Application Number
- CN202411820184.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing sulfur-silver germanium ore electrolytes are easy to decompose at high voltages, resulting in a degradation of electrical properties and incompatible with lithium metal, resulting in a short circuit in the lithium dendrites penetrating the battery.
The method of co-burning different sulfur-silver germanium ore solid electrolytes is adopted to integrate the advantages of a variety of electrolyte materials, and a hybrid ion-electronic conductive interlayer is constructed at the interface between the electrolyte and lithium metal to inhibit the growth of lithium dendrites. At the same time, the addition of specific fluxes reduces the melting point of the electrolyte and optimizes the sintering process.
Effectively inhibit the growth of lithium dendrites, improve battery performance and safety, extend the recycling life of all-solid lithium metal batteries, and reduce manufacturing costs.
Smart Images

Figure CN119650825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of all-solid-state battery electrolyte materials, and in particular to the preparation of a co-fired argyrodite-type electrolyte and an all-solid-state lithium metal battery. Background Art
[0002] Argento-germanite-type electrolyte is a solid electrolyte material with excellent ionic conductivity and has broad application prospects in the field of medium-temperature fuel cells.
[0003] Compared with traditional liquid electrolytes, argyrodite-type electrolytes have the following advantages:
[0004] Solid-state: avoids leakage and corrosion problems of liquid electrolyte, improving battery safety and reliability.
[0005] High ionic conductivity: It has high ionic conductivity at moderate temperatures (300-500°C), which can reduce the operating temperature and energy consumption of the battery.
[0006] Good chemical stability: It has good chemical stability for fuel cell electrode materials and can extend the service life of the battery.
[0007] Although argyrodite electrolytes have many advantages, they also have some disadvantages: argyrodite electrolytes decompose under high voltage, resulting in a decrease in electrical performance. This limits their application in high-temperature fuel cells. They are also incompatible with lithium metal, causing lithium dendrites to penetrate the battery and cause a short circuit.
[0008] Existing technologies also attempt to reduce the interface impedance by doping various elements and performing interface modification, or to perform complex three-dimensional structural design on the lithium metal negative electrode, and to construct an artificial SEI film to inhibit the growth of lithium dendrites. Although these methods have achieved some results to a certain extent, they often have problems such as complex preparation process, high cost, and difficulty in large-scale production, which limits their practical application value.
[0009] 201910557927.8 discloses a method for preparing a sulfide solid electrolyte ceramic with high conductivity, comprising the following steps: in a dry environment protected by inert gas, mixing the raw materials for preparing the sulfide solid electrolyte with a sintering aid, grinding them once, and forming them to obtain a sulfide solid electrolyte sheet, which is then sintered to obtain a sulfide solid electrolyte ceramic with high conductivity; the sulfide solid electrolyte comprises one of a binary sulfide solid electrolyte glass ceramic and a ternary sulfide solid electrolyte ceramic; the porosity of the sulfide solid electrolyte sheet is 7-12%; the sintering treatment temperature is 220-620°C, and the sintering treatment time is 30min-8h; the water content of the dry environment is less than 100ppm. However, the interfacial compatibility between the electrolyte synthesized by this method and lithium metal is poor. Complex chemical reactions are likely to occur between the electrolyte and lithium metal to generate an interfacial layer, making it difficult to form a stable mixed ion-electron conductive interfacial layer. Instead, the electrolyte decomposes into Li3P, which usually has a high resistance, hindering the transmission of lithium ions and may even lead to interface instability. Due to the existence of this interfacial phase, the inhomogeneity of the electrolyte, and the uneven current distribution, the electric field is concentrated in a local area, causing lithium ions to preferentially deposit in high electric field areas, forming lithium dendrites. Lithium dendrites can easily penetrate the electrolyte, causing the battery to short-circuit. Summary of the invention
[0010] In view of this, the present invention provides a preparation method of a co-fired argyrodite-type electrolyte and an all-solid-state lithium metal battery. The invention aims to overcome the shortcomings of existing argyrodite-type electrolytes and all-solid-state lithium metal battery technologies. By adopting the strategy of co-firing different argyrodite-type solid electrolytes, the advantages of different electrolyte materials are successfully integrated, and a unique mixed ion-electron conductive interlayer is constructed at the interface between the co-fired electrolyte and the lithium metal, which effectively inhibits the growth of lithium dendrites and improves the battery performance and safety. In addition, the addition of a specific flux can reduce the melting point of the electrolyte mixture, so that sintering can be achieved at a lower temperature, thereby reducing damage to the electrolyte and improving the sintering efficiency. The diffusion between reactants can be accelerated, the solid phase reaction can be promoted, and the sintering time can be shortened; the formation of a specific crystalline phase can also be promoted, and the generation of a miscellaneous phase can be inhibited, thereby improving the electrochemical properties of the material. That is, the addition of a specific flux optimizes the sintering process, greatly shortens the preparation time, reduces energy consumption, and improves the electrolyte performance from multiple aspects, providing a new direction and effective solution for the development of all-solid-state lithium metal battery technology.
[0011] The co-fired argyrodite solid electrolyte can combine the advantages of different electrolyte materials and overcome the disadvantages of a single electrolyte material. The co-fired argyrodite type of the present invention can be applied to all-solid-state lithium metal batteries and can still maintain more than 90% of the capacity after 500 cycles, greatly improving the cycle life.
[0012] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0013] <First aspect>
[0014] A method for preparing a co-fired argyrodite-type electrolyte comprises the following steps:
[0015] Step 1: Mixing a raw material of a thiourea-type electrolyte and a flux; wherein the raw material of a thiourea-type electrolyte is selected from Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5F 0.7 Cl 0.3 Any two of the following; the flux is selected from at least one of lithium chloride, lithium bromide, lithium iodide, lithium phosphate, silicon oxide, and sodium borate; the molar ratio of the flux is 5%-10% of the argyrodite-type electrolyte raw material;
[0016] Step 2, sintering the mixed materials in step 1 to obtain the co-fired argyrodite-type electrolyte;
[0017] Sintering conditions: 450-500℃ for 2-3 hours.
[0018] In step 2, before sintering, the mixed electrolyte is pressed into a sheet or column; the pressing pressure is 400-500 MPa, and the pressing time is 2-5 minutes.
[0019] The particle size of the argyrodite-type electrolyte raw material is 1-8 μm.
[0020] The application of co-fired argyrodite-type electrolyte in all-solid-state lithium metal secondary batteries with lithium metal as the negative electrode also falls within the protection scope of the present invention.
[0021] Preferably, the argyrodite-type electrolyte is Li6PS5Cl or Li6PS5Br.
[0022] Preferably, the molar ratio of Li6PS5Cl, Li6PS5Br and flux is (1:1:0.1-0.2).
[0023] The content of flux has a significant impact on the performance of co-fired electrolytes. If the flux content is too little, it cannot fully play its role in reducing the melting point and promoting the reaction, resulting in insufficient sintering and reduced material performance. If the flux content is too much, it will introduce too many impurities, affect the purity of the electrolyte, reduce its ionic conductivity, and may even form new phases, which is not conducive to the performance of the electrolyte.
[0024] <Second Aspect>
[0025] An all-solid-state lithium metal secondary battery comprises a negative electrode, a positive electrode and the above-mentioned co-fired argyrodite-type electrolyte, wherein the negative electrode comprises a lithium metal negative electrode or a metal lithium composite negative electrode.
[0026] Compared with the all-solid-state lithium metal battery in the prior art, the beneficial effects of the present invention are:
[0027] 1. In view of the many problems existing in a single electrolyte, such as limited ionic conductivity, poor compatibility with electrode materials, insufficient stability under high voltage, and difficulty in effectively inhibiting the growth of lithium dendrites, the present invention adopts a method of co-firing different argyrodite-type solid electrolytes. This method successfully integrates the advantages of different electrolyte materials and effectively overcomes the defects of a single material. Different argyrodite-type electrolytes have their own characteristics in terms of ion conduction mechanism, chemical stability, etc., and co-firing can achieve performance complementarity, so that the comprehensive performance of the resulting electrolyte is significantly improved. At the contact interface between the co-fired argyrodite-type electrolyte and lithium metal, a unique mixed ion-electron conductive interlayer is constructed. This stable second interface layer is like a solid barrier that can effectively inhibit the growth of lithium dendrites. Lithium dendrites are one of the key factors leading to performance degradation and safety hazards of lithium metal batteries. By inhibiting their growth, the present invention greatly extends the cycle life of all-solid-state lithium metal batteries and significantly improves the overall performance and safety of the battery.
[0028] 2. Compared with the traditional methods of reducing interface impedance such as doping and interface modification, and the complex means of designing the three-dimensional structure of lithium metal or constructing an artificial SEI film to inhibit lithium dendrites, the preparation method of the present invention has obvious advantages. The preparation method of the present invention is simple and easy to implement, does not require complex process equipment and cumbersome operation steps, and is easy to promote and apply on a large scale.
[0029] 3. The present invention has low cost and effectively reduces the manufacturing cost of the battery while ensuring the efficient suppression of lithium dendrites, improves the cost performance of the battery, and provides strong technical support for the industrial development of all-solid-state lithium metal batteries.
[0030] 4. The present invention has conducted in-depth research and found that specific fluxes (such as lithium chloride, lithium bromide, lithium iodide, lithium phosphate, silicon oxide, sodium borate) play a key role in the preparation of argyrodite-type electrolytes. The addition of these fluxes can significantly change the physical and chemical behavior of the material during the sintering process. With the help of fluxes, the present invention successfully optimizes the sintering conditions to a relatively low temperature range of 450-500°C for 2-3 hours to prepare high-quality argyrodite-type electrolytes. Compared with traditional preparation methods, this significantly shortened sintering time not only greatly improves production efficiency, but also achieves a significant reduction in energy consumption, which is in line with the concept of green and efficient modern industrial production.
[0031] 5. Further research of the present invention found that not all fluxes can achieve good results. Lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide (LiI), lithium phosphate (Li3PO4), silicon oxide (SiO2), sodium borate (NaBO2) can effectively reduce the melting point of argyrodite, promote liquid phase reaction, improve the density of materials, and increase the number of lithium ion migration; they can also stabilize the lattice structure of argyrodite, inhibit the volatilization of sulfur, and improve the chemical stability of materials; at the same time, they can also adjust the electronic conductivity of argyrodite, reduce interface impedance, and improve the rate performance of batteries; while Al2O 3、 Li2O and KBO2 have poor effects in these three aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0033] Figure 1 This is the crystal structure diagram of the co-fired argyrodite-type electrolyte;
[0034] Figure 2 This is the XRD pattern of the co-fired argyrodite-type electrolyte of Example 1;
[0035] Figure 3 This is a cycle performance diagram of the co-fired argyrodite-type electrolyte applied to all-solid-state lithium metal in Example 1;
[0036] Figure 4 This is a diagram of the coulombic efficiency of the co-fired argyrodite-type electrolyte applied to an all-solid-state lithium metal battery in Example 2;
[0037] Figure 5 This is a surface scanning electron microscope image of the all-solid-state lithium metal after cycling in Example 1.
[0038] Figure 6 This is a surface scanning electron microscope image of comparative example 4 after all-solid-state lithium metal cycling.
[0039] Figure 7 These are optical photographs of the co-fired electrolytes of Comparative Example 9 without adding flux and at different sintering times, A is sintered for 2 hours; B is sintered for 8 hours. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0041] The crystal structure of the co-fired argyrodite-type electrolyte provided by the present invention is as follows: Figure 1 .
[0042] Example 1
[0043] The present embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in the present embodiment is Li6PS5Cl and Li6PS5I, and the flux is LiI.
[0044] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0045] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5I electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0046] Temperature: 80°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0047] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0048] Time: 12 hours.
[0049] Atmosphere: high purity argon.
[0050] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5I electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5I powder is 1-8μm.
[0051] S3. Mixing evenly: weigh 1 mmol of dried and crushed Li6PS5Cl and Li6PS5I electrolyte powders respectively to form a mixture, and add LiI flux accounting for 5% of the mixture in molar ratio to mix evenly, and the molar ratio of Li6PS5Cl, Li6PS5I, and LiI is 1:1:0.1; S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. Use a tablet press to press, and control the pressing pressure and molding size; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0052] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0053] S6. Sintering: 480℃ for 2 hours.
[0054] Example 2
[0055] The present embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in the present embodiment is Li6PS5Cl and Li6PS5Br, and the flux is LiI.
[0056] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0057] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5Br electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0058] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0059] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0060] Time: 12 hours.
[0061] Atmosphere: high purity argon or vacuum.
[0062] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5Br electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5Br powder is 1-8μm.
[0063] S3. Mixing evenly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and LiI flux was added for even mixing, the molar ratio of Li6PS5Cl, Li6PS5Br, and LiI was 1:1:0.1;
[0064] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0065] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0066] S6. Sintering: 480℃ for 2 hours.
[0067] Figure 2 This is the XRD diagram of the co-fired argyrodite-type electrolyte of Example 1.
[0068] Example 3
[0069] This embodiment provides a co-fired argyrodite electrolyte and a preparation method thereof. The argyrodite electrolyte used in this embodiment is Li6PS5F 0.7 Cl 0.3 and Li6PS5Br, the flux is LiI.
[0070] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0071] S1. Material drying: Due to its hygroscopicity, Li6PS5F 0.7 Cl 0.3 , Li6PS5Br electrolyte powder easily absorbs moisture in the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0072] Temperature: 80°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0073] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0074] Time: 12 hours.
[0075] Atmosphere: Vacuum.
[0076] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, Li6PS5F 0.7 Cl 0.3, Li6PS5Br electrolyte powder is crushed and ground. A ball mill, grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; Li6PS5F 0.7 Cl 0.3 The particle size of the powder is 1-8 μm, and the particle size of the Li6PS5Br powder is 1-8 μm.
[0077] S3. Mix evenly: Mix the dried and crushed Li6PS5F 0.7 Cl 0.3 1 mmol of each Li6PS5Br electrolyte powder was weighed and mixed, and LiI flux was added to mix evenly. 0.7 Cl 0.3 The molar ratio of Li6PS5Br and LiI is 1:1:0.1;
[0078] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0079] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0080] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0081] Example 4
[0082] This embodiment provides a co-fired argyrodite electrolyte and a preparation method thereof. The argyrodite electrolyte used in this embodiment is Li6PS5F 0.7 Cl 0.3 and Li6PS5I, the flux is LiI.
[0083] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0084] S1. Material drying: Due to its hygroscopicity, Li6PS5F 0.7 Cl 0.3 , Li6PS5I electrolyte powder easily absorbs moisture in the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0085] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0086] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0087] Time: 12 hours;
[0088] Atmosphere: high purity argon.
[0089] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, Li6PS5F 0.7 Cl 0.3 , Li6PS5I electrolyte powder is crushed and ground. A ball mill, grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; Li6PS5F 0.7 Cl 0.3 The particle size of the powder is 1-8 μm, and the particle size of the Li6PS5I powder is 1-8 μm;
[0090] S3. Mix evenly: Mix the dried and crushed Li6PS5F 0.7 Cl 0.3 1 mmol of Li6PS5I electrolyte powder was weighed and mixed, and LiI flux was added to mix evenly; Li6PS5F 0.7 Cl 0.3 The molar ratio of Li6PS5I and LiI is 1:1:0.1;
[0091] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press or other equipment can be used for pressing, and the pressing pressure and molding size can be controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0092] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0093] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0094] Example 5
[0095] The present embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in the present embodiment is Li6PS5Cl and Li6PS5Br, and the flux is LiCl.
[0096] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0097] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5Br electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0098] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0099] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0100] Time: 12 hours.
[0101] Atmosphere: Vacuum.
[0102] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5Br electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5Br powder is 1-8μm.
[0103] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and LiCl flux was added for uniform mixing, and the molar ratio of Li6PS5Cl, Li6PS5Br and LiCl was limited to 1:1:0.1;
[0104] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0105] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0106] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0107] Example 6
[0108] The present embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in the present embodiment is Li6PS5Cl and Li6PS5Br, and the flux is LiBr.
[0109] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0110] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5Br electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0111] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0112] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0113] Time: 12 hours.
[0114] Atmosphere: high purity argon or vacuum.
[0115] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5Br electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5Br powder is 1-8μm.
[0116] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and LiBr flux was added for uniform mixing, and the molar ratio of Li6PS5Cl, Li6PS5Br and LiBr was limited to 1:1:0.1;
[0117] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press or other equipment can be used for pressing, and the pressing pressure and molding size can be controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0118] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0119] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0120] Example 7
[0121] The present embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in the present embodiment is Li6PS5Cl and Li6PS5Br, and the flux is LiCl.
[0122] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0123] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5Br electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0124] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0125] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0126] Time: 12 hours.
[0127] Atmosphere: high purity argon or vacuum.
[0128] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5Br electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5Br powder is 1-8μm.
[0129] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and LiF flux was added for uniform mixing, and the molar ratio of Li6PS5Cl, Li6PS5Br and LiF was limited to 1:1:0.2;
[0130] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0131] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0132] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0133] Comparative Example 1
[0134] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that Li6PS5I is replaced by Li 10 GeP2S 12 .
[0135] The argyrodite electrolyte used in this comparative example is Li6PS5Cl and Li 10 GeP2S 12 , the flux is LiI.
[0136] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0137] S1. Material drying: Due to hygroscopicity, Li6PS5Cl, Li 10 GeP2S 12 Electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0138] Temperature: 80°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0139] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0140] Time: 12 hours.
[0141] Atmosphere: high purity argon.
[0142] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, Li6PS5Cl, Li 10 GeP2S 12 The electrolyte powder is crushed and ground. A ball mill, grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size. In this embodiment, a ball mill is used for crushing; the particle size of Li6PS5Cl powder is 1-8 μm, and Li 10 GeP2S 12 The particle size of the powder is 1-8 μm.
[0143] S3. Mix evenly: dry and crush Li6PS5Cl, Li 10 GeP2S 12 1 mmol of each electrolyte powder was weighed and mixed, and LiI flux was added at a molar ratio of 5% of the mixture to mix evenly. 10 GeP2S 12 , the molar ratio of LiI is 1:1:0.1;
[0144] S4-S6 are the same as in Example 1.
[0145] Comparative Example 2
[0146] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 4 is that Li6PS5I is replaced by Li 10 GeP2S 12 .
[0147] The argyrodite electrolyte used in this embodiment is Li6PS5F 0.7 Cl 0.3 and Li 10 GeP2S 12 , the flux is LiI.
[0148] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0149] S1. Material drying: Due to its hygroscopicity, Li6PS5F 0.7 Cl 0.3 , Li 10 GeP2S 12 Electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0150] Temperature: 80-120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0151] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0152] Time: 12 hours.
[0153] Atmosphere: high purity argon or vacuum.
[0154] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, Li6PS5F 0.7 Cl 0.3 , Li 10 GeP2S 12 The electrolyte powder is crushed and ground. A ball mill, grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; in this embodiment, a ball mill is used for crushing; Li6PS5F 0.7 Cl 0.3 The particle size of the powder is 1-8 μm, Li 10 GeP2S 12 The particle size of the powder is 1-8 μm.
[0155] S3. Mix evenly: Mix the dried and crushed Li6PS5F 0.7 Cl 0.3 , Li 10 GeP2S 12 1 mmol of each electrolyte powder was weighed and mixed, and LiI flux was added at a molar ratio of 5% of the mixture to mix evenly. 0.7 Cl 0.3 , Li 10 GeP2S 12 , the molar ratio of LiI is 1:1:0.1;
[0156] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0157] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0158] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0159] Comparative Example 3
[0160] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 5 is that LiCl is replaced by Al2O3, the argyrodite electrolyte used in this comparative example is Li6PS5Cl and Li6PS5Br, and the flux is Al2O3.
[0161] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0162] S1-S2 are the same as in Example 5.
[0163] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and Al2O3 flux was added for uniform mixing, and the molar ratio of Li6PS5Cl, Li6PS5Br, and Al2O3 was limited to 1:1:0.1;
[0164] S4-S6. Same as Example 5.
[0165] Comparative Example 4
[0166] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between the comparative example and Example 5 is that LiCl is replaced by Li2O , The argyrodite electrolytes used in this comparative example are Li6PS5Cl and Li6PS5Br, and the flux is Li2O.
[0167] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0168] S1-S2 are the same as in Example 5.
[0169] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and a 5% molar ratio of Li2O flux was added to the mixture and mixed uniformly, and the molar ratio of Li6PS5Cl, Li6PS5Br, and Li2O was limited to 1:1:0.1;
[0170] S4-S6. Same as Example 5.
[0171] Comparative Example 5
[0172] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between the comparative example and Example 5 is that LiCl is replaced by KBO2, the argyrodite electrolyte used in this comparative example is Li6PS5Cl and Li6PS5Br, and the flux is KBO2.
[0173] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0174] S1-S2 are the same as in Example 5.
[0175] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and KBO2 flux was added for uniform mixing, and the molar ratio of Li6PS5Cl, Li6PS5Br and KBO2 was limited to 1:1:0.1;
[0176] S4-S6. Same as Example 5.
[0177] Comparative Example 6
[0178] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The argyrodite electrolyte used in this comparative example is Li6PS5Cl and Li6PS5Br, and the flux is LiBO2.
[0179] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0180] S1-S2 are the same as in Example 5.
[0181] S3. Mixing uniformly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and a 5% molar ratio of LiI flux was added to the mixture and mixed uniformly, and the molar ratio of Li6PS5Cl, Li6PS5Br, and LiBO2 was limited to 1:1:0.1;
[0182] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press or other equipment can be used for pressing, and the pressing pressure and molding size can be controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0183] S4-S6. Same as Example 5.
[0184] Comparative Example 7
[0185] The difference between this comparative example and Example 7 is that in step S3, the molar ratio of Li6PS5Cl, Li6PS5Br, and LiCl is 1:1:0.05;
[0186] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press or other equipment can be used for pressing, and the pressing pressure and molding size can be controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0187] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0188] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0189] Comparative Example 8
[0190] The difference between this comparative example and Example 7 is that in step S3, the molar ratio of Li6PS5Cl, Li6PS5Br and LiCl is 1:1:0.25; the remaining steps are the same as Example 7.
[0191] Comparative Example 9
[0192] The difference between this comparative example and Example 7 is that in step S3, LiCl is not added, and the remaining steps are the same as Example 7.
[0193] In this comparative example, at the same sintering time as Example 7, the solid phase reaction is incomplete, and it can be clearly seen that the electrolytes of different components undergo phase separation, which affects the uniformity of the material. It is not ruled out that impurities other than the argyrodite structure are generated by the reaction. When the sintering time is extended to 8 hours, the state of the co-fired electrolyte completes the phase transition of a single component from the phase separation of different components, and the impurity phase is not obvious. Figure 7 These are optical photographs of the co-fired electrolytes of Comparative Example 9 without adding flux and at different sintering times, A is sintered for 2 hours; B is sintered for 8 hours.
[0194] Comparative Example 10
[0195] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 2 is that Li6PS5Br is replaced by Li6PS5Cl.
[0196] The argyrodite electrolytes used in this embodiment are Li6PS5Cl and Li6PS5Cl, and the flux is LiI.
[0197] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0198] S1. Material drying: Due to its hygroscopicity, Li6PS5Cl electrolyte powder easily absorbs moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0199] Temperature: 80-120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0200] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0201] Time: 12 hours.
[0202] Atmosphere: high purity argon or vacuum.
[0203] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl electrolyte powder needs to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8 μm.
[0204] S3. Mixing evenly: The dried and crushed Li6PS5Cl electrolyte powder was weighed and mixed by 2mmol, and a 5% molar ratio of LiI flux was added to the mixture and mixed evenly, and the molar ratio of Li6PS5Cl and LiI was limited to 2:0.1;
[0205] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0206] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0207] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0208] Comparative Example 11
[0209] This comparative example provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 2 is that Li6PS5Cl is replaced by Li6PS5Br.
[0210] The argyrodite electrolyte used in this embodiment is Li6PS5Br, and the flux is LiI.
[0211] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0212] S1. Material drying: Due to its hygroscopicity, Li6PS5Cl electrolyte powder easily absorbs moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0213] Temperature: 80-120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0214] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0215] Time: 12 hours.
[0216] Atmosphere: high purity argon or vacuum.
[0217] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Br electrolyte powder needs to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; the present embodiment uses a ball mill for crushing; the particle size of the Li6PS5Br powder is 1-8 μm.
[0218] S3. Mixing evenly: The dried and crushed Li6PS5Br electrolyte powder was weighed and mixed by 2mmol, and a 5% molar ratio of LiI flux was added to the mixture and mixed evenly, and the molar ratio of Li6PS5Br and LiI was limited to 2:0.1;
[0219] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0220] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0221] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0222] Comparative Example 12
[0223] This comparative example provides a co-fired argyrodite electrolyte and a preparation method thereof. The difference between this comparative example and Example 2 is that the argyrodite electrolyte used is Li6PS5Cl 0.5 Br 0.5 .
[0224] The argyrodite electrolyte used in this embodiment is Li6PS5Cl 0.5 Br 0.5 , the flux is LiI.
[0225] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0226] S1. Material drying: Due to its hygroscopicity, Li6PS5Cl 0.5 Br 0.5Electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0227] Temperature: 80-120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0228] Vacuum degree: 10 -3 Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0229] Time: 12 hours.
[0230] Atmosphere: high purity argon or vacuum.
[0231] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, Li6PS5Cl 0.5 Br 0.5 The electrolyte powder is crushed and ground. A ball mill, grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; in this embodiment, a ball mill is used for crushing; Li6PS5Cl 0.5 Br 0.5 The particle size of the powder is 1-8 μm.
[0232] S3. Mix evenly: dry and crushed Li6PS5Cl 0.5 Br 0.5 2 mmol of electrolyte powder was weighed and mixed, and LiI flux was added at a molar ratio of 5% of the mixture to mix evenly. 0.5 Br 0.5 , the molar ratio of LiI is 2:0.1;
[0233] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0234] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0235] S6. Sintering; wherein the sintering conditions are: keeping at 480°C for 2 hours.
[0236] Comparative Example 13
[0237] This embodiment provides a co-fired argyrodite-type electrolyte and a preparation method thereof. The difference between this comparative example and Example 2 is that Li6PS5Cl and Li6PS5Br are synthesized from the raw material end and then co-fired.
[0238] The preparation method of the Li6PS5Cl electrolyte comprises the following steps:
[0239] S1. Raw material preparation and mixing: Li2S, P2S5 and LiCl were weighed according to the stoichiometric ratio and mixed evenly in a ball mill;
[0240] S2. Mechanical ball milling: The mixture is placed in a ball mill to improve the reaction activity through the grinding action of the ball milling medium;
[0241] S3. High temperature reaction: The pre-calcined sample is reacted at high temperature (500°C, 8h) to generate Li6PS5Cl;
[0242] S4. Cooling and crushing: After natural cooling, the product is crushed into fine particles.
[0243] The preparation method of the Li6PS5Br electrolyte comprises the following steps:
[0244] S1. Raw material preparation and mixing: Li2S, P2S5 and LiBr were weighed according to the stoichiometric ratio and mixed evenly in a ball mill;
[0245] S2. Mechanical ball milling: The mixture is placed in a ball mill to improve the reaction activity through the grinding action of the ball milling medium;
[0246] S3. High temperature reaction: The pre-calcined sample is reacted at high temperature (500°C, 8h) to generate Li6PS5Cl;
[0247] S4. Cooling and crushing: After natural cooling, the product is crushed into fine particles.
[0248] The preparation method of the co-fired argyrodite-type electrolyte comprises the following steps:
[0249] S1. Material drying: Due to their hygroscopicity, Li6PS5Cl and Li6PS5Br electrolyte powders easily absorb moisture from the air. The presence of moisture will reduce the fluidity and reactivity of the mixture during co-firing and may cause defects in the product. Therefore, before co-firing, these electrolyte powders need to be dried to constant weight in a vacuum drying oven to remove moisture; specific drying conditions:
[0250] Temperature: 120°C. This temperature range is relatively mild and can effectively remove moisture without damaging the material.
[0251] Vacuum degree: 10 -3Pa. A higher vacuum degree helps to accelerate the evaporation of water.
[0252] Time: 12 hours.
[0253] Atmosphere: high purity argon or vacuum.
[0254] S2. Crushing and grinding: In order to obtain a uniform mixture and increase the reaction area, the Li6PS5Cl and Li6PS5Br electrolyte powders need to be crushed and ground. A ball mill, a grinder or other equipment can be used for crushing, and the crushed powder is sieved and graded to obtain a powder with uniform particle size; this embodiment uses a ball mill for crushing; the particle size of the Li6PS5Cl powder is 1-8μm, and the particle size of the Li6PS5Br powder is 1-8μm.
[0255] S3. Mixing evenly: The dried and crushed Li6PS5Cl and Li6PS5Br electrolyte powders were weighed 1 mmol each and mixed, and LiI flux was added for even mixing, the molar ratio of Li6PS5Cl, Li6PS5Br, and LiI was 1:1:0.1;
[0256] S4. Pressing and molding: In order to facilitate the operation and control during the co-firing process, the mixed electrolyte powder is pressed into a sheet or column shape. A tablet press is used for pressing, and the pressing pressure and molding size are controlled; the pressing pressure is 400Mpa, the pressing time is 2 minutes, and the tablet thickness is 0.4 cm.
[0257] S5. Place the pressed sheet in a quartz tube coated with a carbon film and perform vacuum sealing.
[0258] S6. Sintering: 480℃ for 2 hours.
[0259] Performance test example:
[0260] The products prepared in the above examples and comparative examples were assembled: in an inert gas glove box with a water and oxygen content of ≤0.01 ppm, the co-fired argyrodite-type electrolyte was taken out after sintering and ground and used as the electrolyte layer. The positive electrode had a NCM811 loading of 10 mg / cm per unit area. -2 The electrode is a lithium metal anode layer, and the battery is assembled into a solid-state lithium metal battery. Finally, the battery is discharged and charged twice at 0.1C, and then the battery is discharged and charged for a long cycle at 0.5C. The battery is tested for the first efficiency, and the capacity retention rate is tested after 500 cycles. The results are shown in Table 1:
[0261] It can be seen from Table 1 that when 5%-10% flux is added to form a co-fired argyrodite-type electrolyte as an electrolyte, it can exert a higher first effect and capacity retention, and improve the performance of the life of all-solid-state lithium metal. Figure 2 It can be seen that the structure of Example 1 is still an Argentum-type electrolyte; Figure 3 It can be seen that its excellent cycle ability and capacity retention rate.
[0262] Table 1
[0263]
[0264]
[0265] Figure 4 This is the Coulomb efficiency diagram of the co-fired argyrodite-type electrolyte applied to all-solid-state lithium metal batteries in Example 2.
[0266] Figure 5 This is a surface scanning electron microscope image of the all-solid-state lithium metal after cycling in Example 1.
[0267] Figure 6 This is a surface scanning electron microscope image of comparative example 4 after all-solid-state lithium metal cycling.
[0268] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a co-fired argyrodite-type electrolyte, characterized in that: The steps include: Step 1: Mixing a raw material of a thiourea-type electrolyte and a flux; wherein the raw material of a thiourea-type electrolyte is selected from Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5F 0.7 Cl 0.3 Any two of the following; the flux is selected from at least one of lithium chloride, lithium bromide, lithium iodide, lithium phosphate, silicon oxide, and sodium borate; the molar ratio of the flux is 5%-10% of the argyrodite-type electrolyte raw material; Step 2, sintering the mixed materials in step 1 to obtain the co-fired argyrodite-type electrolyte; Sintering conditions: 450-500℃ for 2-3 hours.
2. The preparation method according to claim 1, characterized in that: Step 2: Before sintering, press the mixed electrolyte into a sheet or column; the pressing pressure is 400-500Mpa, and the pressing time is 2-5 minutes.
3. The preparation method according to claim 1, characterized in that: The particle size of the argyrodite-type electrolyte raw material is 1-8 μm.
4. A co-fired argyrodite-type electrolyte prepared by the preparation method according to any one of claims 1 to 3.
5. Use of a co-fired argyrodite-type electrolyte prepared by the preparation method according to any one of claims 1 to 3 in an all-solid-state lithium metal battery.
6. An all-solid-state lithium metal secondary battery, characterized in that: It comprises a negative electrode, a positive electrode and the co-fired argyrodite-type electrolyte as claimed in claim 5.
7. The all-solid-state lithium metal secondary battery according to claim 6, characterized in that: The negative electrode includes a lithium metal negative electrode or a metal lithium composite negative electrode.